An Integrated Dynamic Closed Loop Simulation Platform for Elbow Flexion Augmentation Using an Upper Limb Exosuit Model - Sambhav, Ratna; Jena, Shreeshan; Chatterjee, Ankit; Bhasin, Shubhendu; Santapuri, Sushma; Kumar, Lalan; Muthukrishnan, Suriya Prakash; Roy, Sitikantha (Frontiers in Robotics and AI, 2022)
Wearable robotic devices are designed to assist, enhance or restore human muscle performance. Understanding how a wearable robotic device changes human biomechanics through complex interaction is important to guide its proper design, parametric optimization, and functional success. The present work develops a human-machine-interaction simulation platform for closed loop dynamic analysis with feedback control and to study the effect of soft-robotic wearables on human physiology. The proposed simulation platform incorporates Computed Muscle Control (CMC) algorithm and is implemented using the MATLAB -OpenSim interface. The framework is generic and will allow the incorporation of any advanced control strategy for wearable devices. As a demonstration, a Gravity Compensation (GC) controller has been implemented on the wearable device and the resulting decrease in the physiological joint moments, muscle activations, and metabolic costs during a simple repetitive load lifting task with two different speeds is investigated